PERBANDINGAN KADAR AIR DAN KADAR MINYAK ATSIRI PADA RIMPANG KENCUR (Kaempferia galangal L.) DENGAN PERBEDAAN PERLAKUAN PENGERINGAN - Mita Anggraini; Gusti Ayu Rai Saputri (Program Studi Analisis Farmasi dan Makanan Universitas Malahayati, 2022)
Kencur rhizome (Kaempferia galangal L.) is widely used as a health drink and traditional medicine in Indonesia. Kencur rhizome is widely used as a medicine for colds, indigestion, analgesic and antipyretic, and beauty because it has the content of essential oils. This research has made simplicia rhizome kencur. The purpose of this study was to determine the ratio of water content and essential oil content in kencur rhizome with different drying treatment. The method used is simple distillation. With the sample treatment is a fresh kencur rhizome after being washed and cleaned of impurities, thinly sliced more or less with a thickness of 3-4 mm. Then each shredded result is dried in two ways, ie with sunlight and oven temperature 50oC. Drying done until dry with moisture content below 10%. Simplicia rhizome kencur, then analyzed water kadai and essential oil content. The results showed that the drying method had significant effect on water content and essential oil content. To get simplicia with relative high volatile oil content can be done by drying using sunlight.